Cultural Components of Film COCO: A Mexican Heritage Multicultural Culture - Vivi Fauziah; Retno Purwani Sari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The aim of this study is to investigate the Mexican cultural components displayed in Pixar Animation Studios’ film Coco. This study examines how cultural practices and maintenances are issued and debated in Mexico, which is known for having the most cultural diversity in America. The study is based on Kennedy and Manohar’s cultural components theory. The qualitative method was used in this study, with note taking used to collect valid data. According to the findings, the film Coco contains seven types of Mexican cultural components: language, religion or belief, norms, cultural values, social collectives, statuses and roles, and cultural integrations. They are all practiced as part of ‘Day of the Dead’ as we known as the Mexican tradition and a part of family traditions. This film’s depiction of multiculturalism has successfully preserved Mexican cultural identity while providing creative and innovative support. Mexican multicultural concepts offer a more comprehensive and useful perspective on today’s world. This study defines how cultural maintenance can support the specific and unique identity of a specific culture. Exploration of arts, culture and heritage, for example, through movies is a potential activity to deal with our senses after a pandemic’s crisis